2021
DOI: 10.1038/s41374-020-00503-3
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear exclusion of YAP exacerbates podocyte apoptosis and disease progression in Adriamycin-induced focal segmental glomerulosclerosis

Abstract: Focal segmental glomerulosclerosis (FSGS) is a chronic glomerular disease with poor clinical outcomes. Podocyte loss via apoptosis is one important mechanism underlying the pathogenesis of FSGS. Recently, Yes-associated-protein (YAP), a key downstream protein in the Hippo pathway, was identified as an activator for multiple gene transcriptional factors in the nucleus to control cell proliferation and apoptosis. To investigate the potential role of YAP in the progression of FSGS, we examined kidney samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
(61 reference statements)
0
12
1
Order By: Relevance
“…Although we did not observe differences in the subcellular localization of YAP before and after ADR treatment, the strong nuclear localization of YAP we observed in the hiPSC-podocytes led us to investigate the expression of YAP’s nuclear cofactors, the TEAD family transcription factors. While others have reported that nuclear YAP is indispensable for human podocyte survival, , it remains unclear which genetic programs YAP is directing in these cells. Thus, we reasoned that studying the YAP-TEAD axis may yield additional insight into the tissue-specific activities of YAP in both injured and healthy podocytes.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although we did not observe differences in the subcellular localization of YAP before and after ADR treatment, the strong nuclear localization of YAP we observed in the hiPSC-podocytes led us to investigate the expression of YAP’s nuclear cofactors, the TEAD family transcription factors. While others have reported that nuclear YAP is indispensable for human podocyte survival, , it remains unclear which genetic programs YAP is directing in these cells. Thus, we reasoned that studying the YAP-TEAD axis may yield additional insight into the tissue-specific activities of YAP in both injured and healthy podocytes.…”
Section: Resultsmentioning
confidence: 98%
“…This nuclear translocation appeared to induce podocyte cell-cycle re-entry and dedifferentiation, an effect we did not observe in this study. It should be noted that in vivo , YAP localization is primarily cytoplasmic in healthy murine podocytes , but nuclear in human podocytes. , In addition to species-specific differences in YAP regulation, matrix stiffness can also govern YAP localization, and thus the activity of downstream YAP targets. In 2018, Bonse and colleagues demonstrated that nuclear YAP is a key regulator of human podocyte survivalwhen the authors plated podocytes on soft matrices (<12 kPa), YAP localized to the cytoplasm, leading to cell detachment and death .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Therefore, podocyte homeostasis relies on a well-balanced nuclear shuttling and activity of YAP and TAZ, a process whose regulation is so far not well understood. 19,[22][23][24][25][26][27] Here, we explore the interactome of YAP and TAZ in an in vitro mouse podocyte model. We identify several nuclear transport components that associate in protein complexes with both YAP and TAZ.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of a key serine (Ser 127) of YAP in mammals confines the protein to the cytoplasm and no longer takes effects in target gene expression, which is regulated by 14-3-3 ζ protein [ 26 ]. YAP has been confirmed to be closely related to renal fibrosis [ 22 , 27 ], cell apoptosis [ 28 ], and epithelial-mesenchymal transition [ 29 ]. Previous study by our team has confirmed that the hucMSC-sEVs-derived 14-3-3 ζ coordinated the Wnt signaling pathway by regulating YAP during skin regeneration [ 30 ].…”
Section: Introductionmentioning
confidence: 99%